MCM3AP and POMP Mutations Cause a DNA‐Repair and DNA‐Damage‐Signaling Defect in an Immunodeficient Child. Issue 3 (30th December 2015) - Gatz, Susanne A.; Salles, Daniela; Jacobsen, Eva‐Maria; Dörk, Thilo; Rausch, Tobias; Aydin, Sevtap; Surowy, Harald; Volcic, Meta; Vogel, Walther; Debatin, Klaus‐Michael; Stütz, Adrian M.; Schwarz, Klaus; et al.
Abstract : Model for the molecular causes underlying immunodeficiency and genome instability promoting malignant transformation in a patient with mono‐allelic mutations in the genes encoding POMP and GANP. While the truncating POMP mutation affects NF‐κB signalling, missense mutated GANP(P443S) leads to reduced AID recruitment and inhibits homologous repair via unbalanced GANP/MCM3AP complex formation. ABSTRACT: Immunodeficiency patients with DNA repair defects exhibit radiosensitivity and proneness to leukemia/lymphoma formation. Though progress has been made in identifying the underlying mutations, in most patients the genetic basis is unknown. Two de novo mutated candidate genes, MCM3AP encoding germinal center‐associated nuclear protein (GANP) and POMP encoding proteasome maturation protein (POMP ), were identified by whole‐exome sequencing (WES) and confirmed by Sanger sequencing in a child with complex phenotype displaying immunodeficiency, genomic instability, skin changes, and myelodysplasia. GANP was previously described to promote B‐cell maturation by nuclear targeting of activation‐induced cytidine deaminase (AID) and to control AID‐dependent hyperrecombination. POMP is required for 20S proteasome assembly and, thus, for efficient NF‐κB signaling. Patient‐derived cells were characterized by impaired homologous recombination, moderate radio‐ and cross‐linker sensitivity associated with accumulation of damage, impaired DNA damage‐induced NF‐κB signaling, and reduced nuclear AID levels. Complementation by wild‐type (WT)‐GANP normalized DNA repair and WT‐POMP rescued defective NF‐κB signaling. In conclusion, we identified for the first time mutations in MCM3AP and POMP in an immunodeficiency patient. These mutations lead to cooperative effects on DNA recombination and damage signaling. Digenic/polygenic mutations may constitute a novel genetic basis in immunodeficiency patients with DNA repair defects.